Adolescent Education as a Strategy to Enhance Knowledge on Iron Supplementation - Ermiati, Ermiati; Widiasih, Restuning; Emaliyawati, Etika; Sutini, Titin; Srimurni, Nita Ayu (Universitas Padjadjaran, 2025)
Iron Supplementation is a crucial intervention for adolescent girls, both in the present and for their future health. Adolescents, particularly females, are at a higher risk of developing anemia compared to other age groups, primarily due to increased blood loss during menstruation. This community engagement initiative aimed to enhance adolescent knowledge regarding the role of iron supplementation in the prevention of anemia. The intervention employed a structured health education program delivered through PowerPoint presentations, informational leaflets, and educational videos. The program was conducted among 36 female students. Data were collected using pre- and post-intervention knowledge assessments, and analyzed by comparing the mean scores before and after the educational session. The findings demonstrated a significant improvement in knowledge, with the mean score increasing from 57.78 in the pre-test to 83.06 in the post-test. Based on these results, it is recommended that iron supplementation education be sustained and integrated into routine school-based supplementation programs to optimize awareness and compliance among adolescent girls.Keywords: Adolescent girls, anemia, blood supplement tablet, health eduacation.